Australian writing programs network : final report. - Webb, Jen; Brien, Donna Lee; Bruns, Axel; Battye, Greg; Williams, Jordan; Bolland, Craig; Smith, Jude (Australian Learning and Teaching Council, 2008)
The project aimed to design, build and maintain an interactive web presence that included: a forum for the discussion of areas of concern; searchable databases of relevant knowledge; and a training mechanism for both students and supervisors. The website thus created aimed to contribute to the learning experience of creative writing candidates by improving standards, consistency and information access, and by relieving the sense of isolation. The Network aimed to raise the profile and recognition of higher degrees learning and teaching, and facilitate strategic change at both institutional and national levels. Moreover, once embedded in Australian universities' programs, the Network is designed to provide effective mechanisms for the identification, development, dissemination and embedding of best practice. The specific outcomes the project sought to achieve were to : initiate a national postgraduate creative writing research and supervision network; promote a culture of collaboration across the creative writing higher education sector in Australia to reduce HDR student isolation and attrition and improve supervision quality; build a national and international research culture among postgraduate research students and their supervisors in creative writing; disseminate information about Australian creative writing higher degrees research, learning and teaching to potential students, early career supervisors, and the publishing community/industry and produce a sustainable and scalable model for use by other creative arts and creative industries disciplines in Australia.